Staurogyne rubescens (Acanthaceae), a new species from southeastern Brazil - Braz, Denise Monte [UNESP]; Monteiro, Reinaldo [UNESP] (My University, 2005)
A new species of Acanthaceae, Staurogyne rubescens, is described and illustrated. It is endemic to the Brazilian moist forests on the eastern range of mountains named Serra do Mar and is thus far known only from the states of Rio de Janeiro and São Paulo. Staurogyne rubescens can be distinguished by its lax terminal racemes, with bracts and bracteoles that are foliaceous, and the flowers that have a pink calyx and red corolla. Staurogyne itatiaiae (Wawra) Leonard also has red flowers and occurs in the highlands of the Atlantic rain forest. The distinguishing characters for these two species are presented in tabular format.
Keywords: Acanthaceae; Brazil; Nelsonioideae; Staurogyne; Calyx; Corolla